Farmers' attitudes and behaviour towards the natural environment : a New Zealand case study : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Ecology at Massey University, Palmerston North, New Zealand - Durpoix, Dorothée (Massey University, 2010)
Scholars from the natural and social sciences have sounded the alarm regarding the future of our productivist society, calling for a change in worldview towards our relationship with the environment. Agriculture rests at the centre of such an issue. Relying on natural resources, it fulfils our basic need for food, yet has caused great damage to this same environment it depends on. Sustainability of farming lies increasingly today in farmers’ ability to generate and export ecologically sound products, while remaining competitive on the international market. The New Zealand farming population represents a particularly good case study. New Zealand’s short human history is associated with one of the highest rates of natural habitat destruction, enabling the country to develop a strong agricultural sector. Today, due to a lack of a comprehensive national legislation, management of native ecosystems on private land depends mainly on private owners’ goodwill. The first of the four objectives of the present research was to assess the general and specific environmental attitudes of farmers in New Zealand. Farmers’ general attitudes towards the natural environment were measured using the New Ecological Paradigm (NEP) scale and the Environmental Motives scale (EMS). Farmers’ specific attitudes towards New Zealand native forest were assessed using the tripartite model of attitude composed of affective, cognitive and conative dimensions. The second objective was to compare the attitudes and context affecting the pro-environmental attitudes of farmers with and without native forest on their farm. The third objective was to assess the pro-environmental attitude-behaviour relationship in farmers with native forest. Finally, the fourth objective was to investigate the context affecting the relationship between pro-environmental attitudes and behaviour in farmers with native forest. It was found that farmers with and without native forest responded to different models of attitude towards native forest. The attitudes of farmers without forest were more cognitively based than those of farmers with forest. Farmers without forest tended to distinguish between native forest on and off the farm, while farmers with forest tended to hold more holistic environmental attitudes. Farmers’ environmental attitudes predicted their behaviour towards their native forest fragments to a similar extent to that usually found in the literature. Direct experience with nature, interactions with one’s family and objective and subjective knowledge were instrumental in predicting the environmental attitudes of all groups of farmers and the behaviour of farmers with native forest.
Keywords: Farming and environment; Agriculture and environment; Forest conservation; Natural resources